Doda-idi Tradition in Aceh: A Socio-Cultural Perspective in Maintaining Cultural Identity in the Midst of Modernity - Inayatillah Inayatillah; Kamaruddin Kamaruddin; Hamidah binti Jalani (Universitas Nurul Jadid, 2025)
The doda-idi tradition is a local Acehnese practice where mothers lull their children in a swing while humming poems filled with prayers, praise, and hopes for their future. Once an essential part of early childhood socialization and character building within Acehnese families, this tradition is now fading. The doda-idi tradition played a crucial role in embedding values and fostering emotional bonds between mother and child. However, it has become increasingly rare among Acehnese families. This article examines the current state of the doda-idi tradition and identifies the factors contributing to its decline. The study employs a qualitative socio-historical approach, utilizing literature reviews, in-depth interviews with mothers, community leaders, and traditional leaders; and field observations to explore the changes in early childhood socialization in Acehnese society. Data were analyzed using Miles and Huberman's analytical techniques, namely, data reduction, data display, and conclusion drawing. Findings reveal two primary factors behind the tradition's decline: modernization and technological advances. Modernization has provided greater educational and employment opportunities for both men and women, leading to increased population mobility. As a result, many women lack exposure to the cultural transmission of doda-idi, which is not taught formally or informally outside family environments. Simultaneously, technological innovations have introduced devices such as electronic swings, tape recorders, and MP3 players, which replace the mother's role in singing doda-idi. The loss of this tradition signifies not only the fading of a cultural practice but also the diminishing of an intimate and significant aspect of early childhood socialization in Acehnese society. Addressing this decline requires efforts to preserve and revive the tradition within the community.